Covid-19 in Indonesia: Critics and Proposal - Jasuma, Nanda Blestri; Krisnadi, Muhammad Faiz (Universitas Muhammadiyah Yogyakarta, 2022)
COVID-19 has been a critical event that we are currently facing. Amidst this uncertain time, the Indonesian government is unable to resist the commercialization practice that exists in medical service, particularly for the COVID-19 cases. In addition to that, intractable neoliberalism led to health inequalities and unequal distribution; uncentralized policy triggered uncontrollable prices. As a result, those practice is harm people in the economic and health sectors. In a simple manner, the COVID-19 outbreak exposed the appalling circumstance of Indonesian healthcare infrastructure resilience. This paper aims to find out the existing commercialization practice of the healthcare service, which should be public goods, and its implication for the people. The research is conducted by utilizing the qualitative research method that includes interviews and secondary data collecting. With the emphasis on criticizing a medical neoliberalism practice, the paper also provides a proposal for the related issue. Regarding the proposals, the paper offers three suggestions: 1) prioritize the preventive measure, 2) prioritize the health budget allocation, and 3) educate people to get used to the self-testing.